Convergence and Divergence of Same-Sex Marriage Policies (A Comparative Study of Constitutional and Administration Law in Three Core Countries of the European Union) - Amania, Malinda Hafizaturrizqo; Yazidi, Nur Syifa (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Same-sex marriage has become one of the most prominent legal and social issues in recent decades, particularly within the European Union, which upholds the principles of non-discrimination and social integration. The Netherlands, France and Germany three core EU member states have all legalized same-sex marriage, yet each through different legal and policy trajectories. This article aims to examine the convergence and divergence of same-sex marriage policies in these countries through a constitutional and administrative law approach. Using a normative juridical method and comparative legal analysis, the study explores how domestic legal frameworks and sociopolitical dynamics shape the regulation of same-sex marriage. The findings indicate that although all three countries now recognize same-sex couples equally under the law, their legislative pathways, earlier forms of legal partnerships (such as registered partnerships and PACS) and their responses to social challenges such as discrimination reflect the distinct legal cultures and constitutional settings of each country. This shows that similar legal outcomes do not always emerge from identical processes, and that local factors continue to play a significant role in shaping legal policy, even in matters of global relevance like same-sex marriage.